El mejoramiento de la práctica docente para el desarrollo de la producción escrita a partir del uso de TIC (2017)
This document describes and analyzes a collaborative work of four teachers of the Municipal Educational Institution Juan XXIII, Facatativá-Cundinamarca, during the period of November 2016 and April 2017, whose objective was to develop and evaluate actions to improve the teaching practice of the teacher Nini Johana Córdoba in the teaching of the writing of a group of fourth grade students with the mediation of Information and Communication Technologies. The research is framed in the qualitative approach, where the object of analysis is the teaching practice. The design corresponds to an action research developed in three cycles of interventions. The theoretical framework is based mainly on two references: on the one hand, the idea of teaching practice as the reflexive exercise performed by the teacher on his actions in the classroom from the dialogue with the theory of his field (Latorre, 2003). On the other hand, the concept of learning the Cultural Historical Activity Theory...